A photochromic material and its preparation method and application

By loading spiropyran onto a silicon aerogel with grafted naphthimide derivatives, the problem of slow color change in the solid state is solved, double light response discoloration is achieved, and the anti-counterfeiting and information encryption capabilities of the material are improved.

CN116023927BActive Publication Date: 2025-02-28ZHEJIANG SCI-TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310128563.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-17
Publication Date
2025-02-28
Estimated Expiration
2043-02-17

AI Technical Summary

Technical Problem

In the solid state, spiropyran has slow or non-discoloration due to dense accumulation, and its light responsiveness is single, making it difficult to effectively encrypt information in practical applications.

Method used

Spiropyran is loaded onto a silicon aerogel with grafted naphthalimide derivatives, and the spiropyran molecules are dispersed by the high specific surface area and porous nature of the silicon aerogel, and the naphthalimide derivatives are introduced to achieve dual photoresponsive discoloration.

Benefits of technology

The color discoloration performance and response sensitivity of spiropyran in solid state are improved, multiple information transformation under alternating ultraviolet light and visible light are realized, and the anti-counterfeiting and information encryption capabilities of the material are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention discloses a photochromic material and a preparation method and application thereof, and belongs to the technical field of organic solid-state photochromic materials. The present invention loads spiropyran in a silicon aerogel grafted with a naphthalimide derivative, and utilizes the porosity of the silicon aerogel to increase the molecular space free volume of the spiropyran molecule, so that the spiropyran has enough space for a ring-opening-ring-closing reaction in the solid state. At the same time, the fluorescent emission wavelength range of the naphthalimide derivative partially overlaps with the ring-opening absorption wavelength range of the spiropyran, and energy transfer can occur between the naphthalimide and the spiropyran, thereby improving the fluorescent color-changing performance of the material, and then realizing the dual color-changing response of the material, which has great application prospects in the fields of anti-counterfeiting, information encryption, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic solid-state photochromic materials, and in particular relates to a photochromic material and a preparation method and application thereof. Background Art

[0002] As a kind of smart material, photoresponsive stimulation materials are widely used in reversible optical data storage, cell detection, ion sensors, anti-counterfeiting, information encryption and other fields. Spiropyran-based photochromic materials are the most promising organic light-stimulation responsive materials. The color-changing mechanism of the core molecule spiropyran is that under the stimulation of ultraviolet light / visible light, its structure can be reversibly converted between colorless closed ring and colored open ring state, but the spiropyran structure is tightly packed in the solid state, and its isomerization ring opening requires a certain free volume. The contradiction between the two makes it difficult for spiropyran to open under the stimulation of external conditions such as ultraviolet light and acid in the solid state, resulting in slow color change or even no color change. However, in practical applications, the color-changing material is usually required to be solid. Therefore, in order to expand its application range, the problem of tight stacking of spiropyran molecules in the solid state needs to be solved urgently. At the same time, the fluorescence color of spiropyran photoisomerization is single, which is easy to be cracked when used to encrypt information. Therefore, upgrading the single light response to dual light response color change can effectively improve the anti-counterfeiting and information encryption capabilities of the material. Summary of the invention

[0003] In order to solve the above problems in the prior art, the present invention provides a photochromic material and a preparation method and application thereof. By loading spiropyran onto a silica aerogel grafted with a naphthalimide derivative, the solid-state photochromic properties of spiropyran are improved while the naphthalimide derivative is introduced to achieve dual color change of the photochromic material.

[0004] To achieve the above object, the present invention provides the following technical solutions:

[0005] One of the technical solutions of the present invention is a photochromic material, which is a silica aerogel loaded with a grafted naphthylimide derivative of spiropyran.

[0006] Furthermore, the structural formula of the naphthaleneimide derivative is:

[0007]

[0008] Wherein, R is -H,

[0009] Furthermore, the silicon aerogel monomer is methyltrimethoxysilane.

[0010] Technical solution 2 of the present invention: The method for preparing the photochromic material comprises the following steps:

[0011] a. Preparation of silica aerogel grafted with naphthalimide derivatives:

[0012] (1) dissolving the naphthaleneimide derivative and the silica aerogel monomer in anhydrous ethanol, and then adding water and HCl solution for hydrolysis;

[0013] (2) adjusting the hydrolyzate obtained in step (1) to alkaline and then allowing it to stand to obtain a gel;

[0014] (3) The gel obtained in step (2) is subjected to solvent replacement, drying, and grinding to obtain the silica aerogel grafted with the naphthalimide derivative;

[0015] b. Loading spiropyran into the silica aerogel grafted with the naphthalimide derivative prepared in step a to obtain the photochromic material:

[0016] (1) preparing a spiropyran tetrahydrofuran solution;

[0017] (2) The silica aerogel grafted with the naphthalimide derivative prepared in step a is mixed with the spiropyran tetrahydrofuran solution prepared in step (1), and the mixture is subjected to ultrasound-assisted solution adsorption to load the spiropyran into the silica aerogel of the naphthalimide derivative to obtain the photochromic material.

[0018] Furthermore, in step a, the molar ratio of the naphthaleneimide derivative to the silicon aerogel monomer is (1-5):(99-95), and the total molar amount of the naphthaleneimide derivative and the silicon aerogel monomer is 100.

[0019] Furthermore, in step a, the ratio of the volume of the anhydrous ethanol, water, and HCl solution to the total molar amount of the naphthaleneimide derivative and the silicon aerogel monomer is 2 mL: 1 mL: 100 μL: 0.01 mol;

[0020] Wherein, the concentration of HCl solution is 1 mol / L.

[0021] Furthermore, in step a, the hydrolysis is carried out by stirring at room temperature with a stirring speed of 1000 rpm for 8 hours.

[0022] Furthermore, in step a, the hydrolyzate is adjusted to be alkaline by adding triethylamine solution (with a concentration of 1 mol / L) to the hydrolyzate until the pH of the hydrolyzate is 8-9.

[0023] Furthermore, in step a, the standing is standing at 80° C. for 2 days.

[0024] Furthermore, in step a, the solvent is replaced by ethanol for immersion, and the immersion time is 2 days.

[0025] Wherein, ethanol is anhydrous ethanol, and the amount of anhydrous ethanol used is 150 ml.

[0026] Furthermore, in step a, the drying is performed at 80° C. for 3 to 6 hours.

[0027] Furthermore, in step a, the grinding is an optional step, the purpose of which is to reduce the blocky gel and facilitate the loading of spiropyran. Omitting the grinding can also achieve the purpose of loading without affecting the loading effect.

[0028] Furthermore, in step b, the concentration of the spiropyran tetrahydrofuran solution is 0.02 to 0.2 mol / L.

[0029] Furthermore, in step b, the mass volume ratio of the silica aerogel grafted with the naphthylimide derivative to the spiropyran tetrahydrofuran solution is 200 mg: (2-4) mL.

[0030] Furthermore, in step b, the ultrasound-assisted solution adsorption is specifically as follows: the mixture is subjected to ultrasound, allowed to stand, and filtered to obtain a filter residue, and the filter residue is washed and dried to obtain the photochromic material;

[0031] The frequency of ultrasound is 40KHz, and the time is 0.5-1h; the standing is 8-24h at room temperature; the washing is eluting with 4-10ml of tetrahydrofuran (pure) for 5-10s; and the drying is vacuum drying at a temperature of 30°C and a vacuum degree of 0.1KPa for 2-8h.

[0032] The third technical solution of the present invention: application of the photochromic material in the field of information anti-counterfeiting and encryption.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] (1) The photochromic material prepared by the present invention has a solid powder whose fluorescence and color change when exposed to ultraviolet light with a wavelength of 365 nm. When exposed to visible light, the color and fluorescence of the powder change inversely. Under the alternating irradiation of ultraviolet light and visible light, multiple information changes can be achieved.

[0035] (2) The photochromic material prepared by the present invention has a sensitive light response and can accurately read or hide information by irradiating ultraviolet light and visible light alternately in a short period of time, thereby increasing the difficulty of information decryption. It is a highly potential next-generation intelligent anti-counterfeiting material.

[0036] (3) The present invention loads spiropyran onto a silica aerogel grafted with a naphthylimide derivative, and utilizes the high specific surface area and porosity of the silica aerogel to disperse the densely packed spiropyran molecules, thereby greatly increasing the free volume of the spiropyran molecules, so that the spiropyran has sufficient space to undergo a ring-opening-ring-closing reaction in the solid state, and the spiropyran has a reversible isomerization ability in the solid state, thereby improving the solid-state color-changing performance of the spiropyran.

[0037] (4) The present invention utilizes the overlap between the fluorescence emission wavelength range of the naphthalimide derivative and the absorption wavelength range of the isomerization ring-opening (MC) of spiropyran. After ultraviolet light irradiation, a resonance transfer of fluorescence energy occurs from the donor naphthalimide derivative to the acceptor isomerization ring-opening of spiropyran, thereby improving the fluorescence color-changing performance of the material, improving the single color-changing performance of spiropyran, and realizing the dual color-changing response of the photochromic material. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0039] Figure 1 It is the overlapping spectrum of the fluorescence emission spectrum of naphthalene imide and the ultraviolet absorption spectrum of spiropyran;

[0040] Figure 2 This is a scanning electron microscope image of the photochromic material prepared in Example 1 of the present invention at a magnification of ×20,000;

[0041] Figure 3 The color change and ultraviolet absorption spectrum of the photochromic material (not discolored) prepared in Example 1 of the present invention when irradiated with ultraviolet light (365nm) for different time periods;

[0042] Figure 4 The color change and ultraviolet absorption spectrum of the photochromic material (already discolored) prepared in Example 1 of the present invention when irradiated with white light for different time periods;

[0043] Figure 5 The fluorescence emission spectra of the photochromic material (not discolored) prepared in Example 1 of the present invention when irradiated with ultraviolet light (365 nm) for different time periods;

[0044] Figure 6 The fluorescence emission spectra of the photochromic material (already discolored) prepared in Example 1 of the present invention when irradiated with white light for different time periods;

[0045] Figure 7 The chromaticity diagram of the photochromic material (not discolored) prepared in Example 1 of the present invention irradiated with ultraviolet light (365 nm) for different time periods;

[0046] Figure 8 The fluorescence emission spectra of the photochromic material (not discolored) prepared in Example 2 of the present invention when irradiated with ultraviolet light (365 nm) for different time periods;

[0047] Fig. 9The fluorescence emission spectra of the photochromic material (already discolored) prepared in Example 2 of the present invention when irradiated with white light for different time periods;

[0048] Fig.10 The chromaticity diagram of the photochromic material (not discolored) prepared in Example 2 of the present invention irradiated with ultraviolet light (365 nm) for different time periods;

[0049] Fig.11 The actual pictures are of the photochromic materials prepared in Examples 1 to 3 and Examples 6 to 7 of the present invention. DETAILED DESCRIPTION

[0050] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0051] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0052] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0053] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0054] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0055] The normal temperature of the present invention refers to 25±2°C.

[0056] Example 1

[0057] a. Preparation of silica aerogel grafted with 2-(3-(triethoxysilyl)propyl)-1,8-naphthalimide:

[0058] (1) 0.0003 mol of 2-(3-(triethoxysilyl)propyl)-1,8-naphthaleneimide and 0.0097 mol of methyltrimethoxysilane were dissolved in 2 mL of anhydrous ethanol, and then 1 mL of ultrapure water and 100 μL of 1 M HCl solution were added, and the mixture was stirred at 1000 rpm for 8 h at room temperature to obtain a hydrolyzate;

[0059] (2) adding triethylamine solution (concentration of 1 mol / L) to the hydrolyzate obtained in step (1) until the pH of the hydrolyzate reaches 8, and then standing at 80° C. for 2 days to obtain a gel;

[0060] (3) soaking the gel obtained in step (2) in anhydrous ethanol for solvent replacement, wherein the soaking time is 2 days and the amount of anhydrous ethanol used is 150 ml; then drying the gel at 80° C. for 3 hours, and grinding it into powder after cooling to room temperature to obtain a silica aerogel grafted with 2-(3-(triethoxysilyl)propyl)-1,8-naphthalimide;

[0061] b. Loading spiropyran into the silica aerogel grafted with 2-(3-(triethoxysilyl)propyl)-1,8-naphthalimide prepared in step a:

[0062] (1) preparing a spiropyran tetrahydrofuran solution with a concentration of 0.1 mol / L;

[0063] (2) 200 mg of the silica aerogel grafted with 2-(3-(triethoxysilyl)propyl)-1,8-naphthalimide prepared in step a is mixed with 2 mL of the spiropyran tetrahydrofuran solution prepared in step (1), the mixture is sonicated, allowed to stand, and filtered to obtain a filter residue, and the filter residue is washed and dried to obtain the photochromic material; wherein the frequency of the ultrasound is 40 KHz and the time is 0.5 h; the standing is 8 h at room temperature; the washing is eluting with 4 mL of tetrahydrofuran for 5 s; and the drying is vacuum drying at a temperature of 30° C. and a vacuum degree of 0.1 KPa for 2 h.

[0064] Example 2

[0065] a. Preparation of silica aerogel grafted with 6-(dimethylamino)-2-(3-(triethoxysilyl)propyl)-1,8-naphthalimide:

[0066] (1) 0.0002 mol of 6-(dimethylamino)-2-(3-(triethoxysilyl)propyl)-1,8-naphthaleneimide and 0.0098 mol of methyltrimethoxysilane were dissolved in 2 mL of anhydrous ethanol, and then 1 mL of ultrapure water and 100 μL of 1 M HCl solution were added, and the mixture was stirred at 1000 rpm for 8 h at room temperature to obtain a hydrolyzate;

[0067] (2) adding triethylamine solution (concentration of 1 mol / L) to the hydrolyzate obtained in step (1) until the pH of the hydrolyzate reaches 8, and then standing at 80° C. for 2 days to obtain a gel;

[0068] (3) soaking the gel obtained in step (2) in anhydrous ethanol for solvent replacement, wherein the soaking time is 2 days and the amount of anhydrous ethanol used is 150 ml; then drying the gel at 80° C. for 4 hours, and grinding it into powder after cooling to room temperature to obtain a silica aerogel grafted with 6-(dimethylamino)-2-(3-(triethoxysilyl)propyl)-1,8-naphthalimide;

[0069] b. Loading spiropyran into the silica aerogel grafted with 6-(dimethylamino)-2-(3-(triethoxysilyl)propyl)-1,8-naphthalimide prepared in step a:

[0070] (1) preparing a spiropyran tetrahydrofuran solution with a concentration of 0.1 mol / L;

[0071] (2) 200 mg of the silica aerogel grafted with 6-(dimethylamino)-2-(3-(triethoxysilyl)propyl)-1,8-naphthalimide prepared in step a is mixed with 2 mL of the spiropyran tetrahydrofuran solution prepared in step (1), the mixture is sonicated, allowed to stand, and filtered to obtain a filter residue, and the filter residue is washed and dried to obtain the photochromic material; wherein the frequency of the ultrasound is 40 KHz and the time is 0.6 h; the standing is 9 h at room temperature; the washing is eluting with 6 mL of tetrahydrofuran for 7 s; and the drying is vacuum drying at a temperature of 30° C. and a vacuum degree of 0.1 KPa for 3 h.

[0072] Example 3

[0073] a. Preparation of silica aerogel grafted with 6-phenyl-2-(3-(triethoxysilyl)propyl)-1,8-naphthalimide:

[0074] (1) 0.0001 mol of 6-phenyl-2-(3-(triethoxysilyl)propyl)-1,8-naphthalimide and 0.0099 mol of methyltrimethoxysilane were dissolved in 2 mL of anhydrous ethanol, and then 1 mL of ultrapure water and 100 μL of 1 M HCl solution were added, and the mixture was stirred at 1000 rpm for 8 h at room temperature to obtain a hydrolyzate;

[0075] (2) adding triethylamine solution (concentration of 1 mol / L) to the hydrolyzate obtained in step (1) until the pH of the hydrolyzate reaches 8, and then standing at 80° C. for 2 days to obtain a gel;

[0076] (3) soaking the gel obtained in step (2) in anhydrous ethanol for solvent replacement, wherein the soaking time is 2 days and the amount of anhydrous ethanol used is 150 ml; then drying the gel at 80° C. for 4 hours, and grinding it into powder after cooling to room temperature to obtain a silica aerogel grafted with 6-phenyl-2-(3-(triethoxysilyl)propyl)-1,8-naphthalimide;

[0077] b. Loading spiropyran into the silica aerogel grafted with 6-phenyl-2-(3-(triethoxysilyl)propyl)-1,8-naphthalimide prepared in step a:

[0078] (1) preparing a spiropyran tetrahydrofuran solution with a concentration of 0.1 mol / L;

[0079] (2) 200 mg of the silica aerogel grafted with 6-phenyl-2-(3-(triethoxysilyl)propyl)-1,8-naphthalimide prepared in step a is mixed with 2 mL of the spiropyran tetrahydrofuran solution prepared in step (1), the mixture is sonicated, allowed to stand, and filtered to obtain a filter residue, and the filter residue is washed and dried to obtain the photochromic material; wherein the frequency of the ultrasound is 40 KHz and the time is 0.8 h; the standing is 12 h at room temperature; the washing is eluting with 10 ml of tetrahydrofuran for 10 s; and the drying is vacuum drying at a temperature of 30° C. and a vacuum degree of 0.1 KPa for 8 h.

[0080] Example 4

[0081] a. Preparation of silica aerogel grafted with 6-(2-thiophene)-2-(3-(triethoxysilyl)propyl)-1,8-naphthalimide:

[0082] (1) 0.0001 mol of 6-(2-thiophene)-2-(3-(triethoxysilyl)propyl)-1,8-naphthaleneimide and 0.0099 mol of methyltrimethoxysilane were dissolved in 2 mL of anhydrous ethanol, and then 1 mL of ultrapure water and 100 μL of 1 M HCl solution were added, and the mixture was stirred at 1000 rpm for 8 h at room temperature to obtain a hydrolyzate;

[0083] (2) adding triethylamine solution (concentration of 1 mol / L) to the hydrolyzate obtained in step (1) until the pH of the hydrolyzate reaches 9, and then standing at 80° C. for 2 days to obtain a gel;

[0084] (3) soaking the gel obtained in step (2) in anhydrous ethanol for solvent replacement, wherein the soaking time is 2 days and the amount of anhydrous ethanol used is 150 ml; then drying the gel at 80° C. for 6 hours, and grinding it into powder after cooling to room temperature to obtain a silica aerogel grafted with 6-(2-thiophene)-2-(3-(triethoxysilyl)propyl)-1,8-naphthalimide;

[0085] b. Loading the spiropyran in the silica aerogel grafted with 6-(2-thiophene)-2-(3-(triethoxysilyl)propyl)-1,8-naphthalimide prepared in step a:

[0086] (1) preparing a spiropyran tetrahydrofuran solution with a concentration of 0.1 mol / L;

[0087] (2) 200 mg of the silica aerogel grafted with 6-(2-thiophene)-2-(3-(triethoxysilyl)propyl)-1,8-naphthalimide prepared in step a is mixed with 2 mL of the spiropyran tetrahydrofuran solution prepared in step (1), the mixture is sonicated, allowed to stand, and filtered to obtain a filter residue, and the filter residue is washed and dried to obtain the photochromic material; wherein the frequency of the ultrasound is 40 KHz and the time is 1 hour; the standing is 15 hours at room temperature; the washing is eluting with 10 mL of tetrahydrofuran for 10 seconds; and the drying is vacuum drying at a temperature of 30° C. and a vacuum degree of 0.1 KPa for 8 hours.

[0088] Example 5

[0089] a. Preparation of silica aerogel grafted with 6-morpholine-2-(3-(triethoxysilyl)propyl)-1,8-naphthalimide:

[0090] (1) 0.0001 mol of 6-morpholine-2-(3-(triethoxysilyl)propyl)-1,8-naphthalimide and 0.0099 mol of methyltrimethoxysilane were dissolved in 2 mL of anhydrous ethanol, and then 1 mL of ultrapure water and 100 μL of 1 M HCl solution were added, and the mixture was stirred at 1000 rpm for 8 h at room temperature to obtain a hydrolyzate;

[0091] (2) adding triethylamine solution (concentration of 1 mol / L) to the hydrolyzate obtained in step (1) until the pH of the hydrolyzate reaches 9, and then standing at 80° C. for 2 days to obtain a gel;

[0092] (3) soaking the gel obtained in step (2) in anhydrous ethanol for solvent replacement, wherein the soaking time is 2 days and the amount of anhydrous ethanol used is 150 ml; then drying the gel at 80° C. for 6 hours, and grinding it into powder after cooling to room temperature to obtain a silica aerogel grafted with 6-morpholine-2-(3-(triethoxysilyl)propyl)-1,8-naphthalimide;

[0093] b. Loading spiropyran into the silica aerogel grafted with 6-morpholine-2-(3-(triethoxysilyl)propyl)-1,8-naphthalimide prepared in step a:

[0094] (1) preparing a spiropyran tetrahydrofuran solution with a concentration of 0.1 mol / L;

[0095] (2) 200 mg of the silica aerogel grafted with 6-morpholine-2-(3-(triethoxysilyl)propyl)-1,8-naphthalimide prepared in step a is mixed with 2 mL of the spiropyran tetrahydrofuran solution prepared in step (1), the mixture is sonicated, allowed to stand, and filtered to obtain a filter residue, and the filter residue is washed and dried to obtain the photochromic material; wherein the frequency of the ultrasound is 40 KHz and the time is 0.5 h; the standing is 8 h at room temperature; the washing is eluting with 4 mL of tetrahydrofuran for 5 s; and the drying is vacuum drying at a temperature of 30° C. and a vacuum degree of 0.1 KPa for 2 h.

[0096] Effect verification:

[0097] The overlapping spectrum of the fluorescence emission spectrum of naphthalene imide and the ultraviolet absorption spectrum of spiropyran is shown in Figure 1 As shown;

[0098] Depend on Figure 1 It can be found that the fluorescence emission wavelength of naphthalene imide overlaps with the absorption wavelength range of spiropyran isomerization ring opening, and energy transfer can occur between 1,8-naphthalene imide and spiropyran, thereby improving the fluorescence color-changing performance of the material and realizing the dual color-changing response of the material.

[0099] The photochromic material prepared in Example 1 was analyzed by scanning electron microscopy at a magnification of ×20000 times. Figure 2 As shown;

[0100] Depend on Figure 2 It can be found that the structure of the photochromic material prepared in Example 1 is mainly formed by the aggregation of amorphous nanoclusters with rich pores, which can disperse the accumulated spiropyran and provide opening space, greatly increasing the free volume of the spiropyran molecules, so that the spiropyran has sufficient space for opening-closing reaction in the solid state, and the spiropyran has reversible isomerization ability in the solid state.

[0101] The photochromic material prepared in Example 1 was irradiated under ultraviolet light (365 nm) for different time periods, and the powder color and absorbance of the photochromic material irradiated for different time periods were tested. The test results are as follows: Figure 3 As shown;

[0102] Depend on Figure 3It can be found that the photochromic material prepared in Example 1 is very sensitive to ultraviolet light (365nm), and there is an obvious change in absorbance within 5s of ultraviolet light (365nm) irradiation. As time goes by, the color of the powder changes from white to purple, and the absorbance increases from 0.23 to about 0.8.

[0103] The photochromic material prepared in Example 1 was first irradiated under 365 nm ultraviolet light for 300 s, and then the discolored photochromic material was irradiated under white light for different time periods, and the powder color and absorbance recovery test of the photochromic material irradiated for different time periods was performed. The test results are shown in FIG. Figure 4 As shown;

[0104] Depend on Figure 4 It can be found that the photochromic material prepared in Example 1 has good reversibility and can almost return to the initial state. Therefore, the photochromic material prepared in Example 1 significantly improves the problem of poor photochromic performance caused by the inability of spiropyran to open the ring in the solid state.

[0105] The photochromic material prepared in Example 1 was irradiated under ultraviolet light (365 nm) for different time periods, and the fluorescence emission spectrum of the photochromic material irradiated for different time periods was tested. The test results are as follows: Figure 5 As shown;

[0106] Depend on Figure 5 It can be found that after the photochromic material prepared in Example 1 was irradiated with 365nm ultraviolet light, the emission peak intensity of naphthylimide at around 450nm gradually decreased and showed a slight blue shift, the ring-opening emission peak of spiropyran at around 630nm continued to red shift, and the emission peak intensity first increased and then decreased, and the fluorescence color changed from blue to red, which proved that the material under the irradiation of 365nm ultraviolet light underwent obvious energy transfer; after analysis, this was due to the J-type stacking of the spiropyran in the ring-opening part of the spiropyran.

[0107] The photochromic material prepared in Example 1 was first irradiated under 365 nm ultraviolet light for 300 s, and then the discolored photochromic material was irradiated under white light for different time periods, and the fluorescence emission spectrum recovery test was performed on the photochromic material irradiated for different time periods. The test results are as follows: Figure 6 As shown;

[0108] Depend on Figure 6 It can be found that: under white light irradiation, the emission peak intensity of naphthylimide around 450nm gradually increases and slightly red-shifts and recovers, the spiropyran ring-opening emission peak around 650nm continues to blue-shift, and the emission peak intensity continues to decrease, and the fluorescence color changes from red to blue, which proves that the material can recover under the irradiation of white light.

[0109] The photochromic material prepared in Example 1 was irradiated under ultraviolet light (365 nm) for different time periods, and the fluorescence colorimetry of the photochromic material irradiated for different time periods was tested. The test results are as follows: Figure 7 As shown;

[0110] Depend on Figure 7 It can be found that: with the irradiation of ultraviolet light, the powder fluorescence changes significantly, the chromaticity coordinates change from (0.21, 0.18) to (0.31, 0.17), and the powder fluorescence changes from the original blue to red, indicating that the fluorescence color change span of the photochromic material prepared in Example 1 is large and very obvious, achieving a dual photochromic response.

[0111] The photochromic material prepared in Example 2 was irradiated under ultraviolet light (365 nm) for different time periods, and the fluorescence emission spectrum of the photochromic material irradiated for different time periods was tested. The test results are as follows: Figure 8 As shown;

[0112] Depend on Figure 8 It can be found that: compared with the photochromic material prepared in Example 1, the naphthalimide emission peak of the photochromic material prepared in Example 2 is significantly red-shifted from about 450nm to about 500nm;

[0113] After the photochromic material prepared in Example 2 was irradiated with 365nm ultraviolet light, the emission peak intensity of naphthylimide around 500nm gradually decreased and showed a slight blue shift, the ring-opening emission peak of spiropyran around 630nm continued to red shift, and the emission peak intensity first increased and then decreased, and the fluorescence color changed from green to red, which proved that the material underwent obvious energy transfer under the irradiation of 365nm ultraviolet light; after analysis, this was due to the J-type stacking of the spiropyran in the ring-opening part of the spiropyran.

[0114] The photochromic material prepared in Example 2 was first irradiated under 365nm ultraviolet light for 300s, and then the discolored photochromic material was irradiated under white light for different time periods, and the fluorescence emission spectrum recovery test was performed on the photochromic material irradiated for different time periods. The test results are as follows: Fig. 9 As shown;

[0115] Depend on Fig. 9 It can be found that: under white light irradiation, the emission peak intensity of naphthylimide around 500nm gradually increases and slightly red-shifts and recovers, the spiropyran ring-opening emission peak around 650nm continues to blue-shift, and the emission peak intensity continues to decrease, and the fluorescence color changes from red to green, which proves that the material can recover under the irradiation of white light.

[0116] The photochromic material prepared in Example 2 was irradiated under ultraviolet light (365 nm) for different time periods, and the fluorescence colorimetry of the photochromic material irradiated for different time periods was tested. The test results are as follows: Fig.10 As shown;

[0117] Depend on Fig.10 It can be found that: with the irradiation of ultraviolet light, the powder fluorescence changes significantly, the chromaticity coordinates change from (0.28, 0.57) to (0.52, 0.36), and the powder fluorescence changes from the original green to red, indicating that the material's fluorescence color change span is large and very obvious, achieving a dual photochromic response.

[0118] The photochromic materials prepared in Examples 3 to 5 were also subjected to the above-mentioned scanning electron microscope analysis, powder color and absorbance test, powder color and absorbance recovery test, fluorescence emission spectrum test and fluorescence emission spectrum recovery test. The test spectra were similar in trend to the test spectra of Examples 1 to 2, which proves that all photochromic materials prepared within the scope of protection of the claims of the present invention can achieve good fluorescence color change and dual color change response.

[0119] Example 6

[0120] The same as Example 1, except that in step a, the amount of 2-(3-(triethoxysilyl)propyl)-1,8-naphthalimide used is 0.0005 mol, and the amount of methyltrimethoxysilane used is 0.0095 mol.

[0121] Example 7

[0122] The same as Example 1, except that in step a, the amount of 2-(3-(triethoxysilyl)propyl)-1,8-naphthalimide used is 0.0004 mol, and the amount of methyltrimethoxysilane used is 0.0096 mol.

[0123] The actual pictures of the photochromic materials prepared in Examples 1 to 3 and Examples 6 to 7 are as follows: Fig.11 As shown;

[0124] Depend on Fig.11 It can be found that: the aerogel system is not uniform and phase separation occurs; the study shows that when the molar ratio of naphthalimide exceeds 3%, although the fluorescence intensity continues to rise, the sol-gel system begins to be non-uniform and phase separation occurs. This is determined by the solubility of naphthalimide in the system. If the concentration is too high, some naphthalimide will not dissolve, and when triethylamine solution is added, the system is more likely to precipitate and stratify, resulting in incomplete gelation during gelation.

[0125] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A photochromic material, characterized in that: The photochromic material is a silica aerogel loaded with a grafted naphthalimide derivative of spiropyran; The structural formula of the naphthaleneimide derivative is: Among them, R is The monomer of the silicon aerogel is methyltrimethoxysilane.

2. A method for preparing the photochromic material according to claim 1, characterized in that: The following steps are involved: a. Preparation of silica aerogel grafted with naphthalimide derivatives: (1) dissolving a naphthaleneimide derivative and a silicon aerogel monomer in anhydrous ethanol, and then adding water and HCl solution for hydrolysis to obtain a hydrolyzate; The molar ratio of the naphthalene imide derivative to the silicon aerogel monomer is (1-3): (99-97); (2) adjusting the hydrolyzate obtained in step (1) to alkaline and then allowing it to stand to obtain a gel; (3) The gel obtained in step (2) is subjected to solvent replacement, drying, and grinding to obtain the silica aerogel grafted with the naphthalimide derivative; b. Loading spiropyran into the silica aerogel grafted with the naphthalimide derivative prepared in step a to obtain the photochromic material: (1) preparing a spiropyran tetrahydrofuran solution; (2) The silica aerogel grafted with the naphthalimide derivative prepared in step a is mixed with the spiropyran tetrahydrofuran solution prepared in step (1), and the mixture is subjected to ultrasound-assisted solution adsorption to load the spiropyran into the silica aerogel of the naphthalimide derivative to obtain the photochromic material.

3. The preparation method according to claim 2, characterized in that: In step a, the ratio of the volume of the anhydrous ethanol, water, and HCl solution to the total molar amount of the naphthalene imide derivative and the silicon aerogel monomer is 2mL:1mL:100μL:0.01mol; the concentration of the HCl solution is 1mol / L, and the hydrolysis is stirred at room temperature for 8h.

4. The preparation method according to claim 2, characterized in that: In step a, the standing is standing at 80° C. for 2 days; and the solvent is replaced by ethanol immersion.

5. The preparation method according to claim 2, characterized in that: In step b, the concentration of the spiropyran tetrahydrofuran solution is 0.02-0.2 mol / L; the mass volume ratio of the silica aerogel grafted with the naphthylimide derivative to the spiropyran tetrahydrofuran solution is 200 mg: (2-4) mL.

6. The preparation method according to claim 2, characterized in that: In step b, the ultrasound-assisted solution adsorption specifically comprises: subjecting the mixture to ultrasound, standing, and filtering to obtain a filter residue, and the filter residue is washed and dried to obtain the photochromic material.

7. The preparation method according to claim 6, characterized in that: The frequency of the ultrasound is 40 KHz, and the time of the ultrasound is 0.5 to 1 hour; the standing is 8 to 24 hours at room temperature; and the washing is eluting with tetrahydrofuran.

8. Application of the photochromic material according to claim 1 in the field of information anti-counterfeiting and encryption.